Replacement of electric resistive space heating by an air-source heat pump in a residential application. Environmental amortization - Latorre-Biel, Juan-Ignacio (2018)
All-electric boilers and air source heat pumps are both powered by electric energy. However, each kWh of heat that is produced implies higher electric consumption in the former. Therefore, as a consequence of ﬁnancial issues, users of all-electric boilers might aﬀord the substitution of this heating device by an air source heat pump (ASHP). In this paper, a particular facet of this replacement is analyzed, its environmental impact, providing with a deeper insight in the consequences of this substitution. A life cycle assessment of the replacement of an all-electric boiler by an ASHP is described, using 11 environmental impact categories and three diﬀerent heat emitters, such as underﬂoor heating, low temperature radiators and conventional radiators. As a consequence of this analysis, it has been found that, in most of the categories, the energy savings from the replacement compensate the environmental impact of the ASHP. This trend is more evident with underﬂoor heating than radiators. Additionally, the environmental amortization of this replacement has also been analyzed. The results of this study show that the environmental amortization can be achieved by an ASHP with underﬂoor heating during a conservative lifespan of 10 years in all the impact categories. Other heat emitters may require between 33% and 45% more time to reach the environmental amortization.